2022
DOI: 10.3390/agriculture12111964
|View full text |Cite
|
Sign up to set email alerts
|

Plant Disease Detection Strategy Based on Image Texture and Bayesian Optimization with Small Neural Networks

Abstract: A novel method of disease diagnosis, based on images that capture every part of a diseased plant, such as the leaf, the fruit, the root, etc., is presented in this paper. As is well known, the plant genotypic and phenotypic characteristics can significantly impact how plants are affected by viruses, bacteria, or fungi that cause disease. Assume that these data are unknown at the outset and that the appropriate precautions are not taken to prevent classifications skewed toward uninteresting traits. An approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The GAP layers [51] output is projected into a classifier called SoftMax. Bayes optimization tests [52] also confirmed that ReLU and dropout have collaboration, which implies that using them together is optimal. To reduce the dropout and overfitting problems on a global scale, Bayesian optimization (BO) is a statistical optimization method.…”
Section: Plos Onementioning
confidence: 76%
“…The GAP layers [51] output is projected into a classifier called SoftMax. Bayes optimization tests [52] also confirmed that ReLU and dropout have collaboration, which implies that using them together is optimal. To reduce the dropout and overfitting problems on a global scale, Bayesian optimization (BO) is a statistical optimization method.…”
Section: Plos Onementioning
confidence: 76%
“…The outcomes of the experiments show how well the suggested method works to correctly identify different plant diseases, which enhances agricultural management techniques. A cloud-enabled platform powered by machine learning algorithms for crop recommendation in precision farming is presented by Thilakarathne et al (2022) [2]. In an effort to maximize farming methods and raise output, the platform uses sensor data and cloud computing to give farmers customized crop advice.The authors create a machine learning-based method for crop recommendation based on sensor data, including soil composition, climate, and past yield information.…”
Section: IImentioning
confidence: 99%
“…Similarly, using the PlantVillage dataset, Restrepo-Arias et al [104] introduced a novel diagnostic approach that highlights the impact of genotypic and phenotypic characteristics on how plants respond to pathogens. Their method, which emphasizes texture-based features and uses Bayesian Optimization to train artificial neural networks, achieved an impressive accuracy of up to 96.31% with MobileNet.…”
Section: Crop Disease Monitoringmentioning
confidence: 99%
“…A major limitation identified is the shortage of large-scale standardized image datasets for the greenhouse domain (as noted in [65], [101], [104]). Most studies rely on small proprietary datasets collected by the researchers themselves, often just a few hundred images, which restricts generalization of techniques ( [92], [97], [106]).…”
Section: ) Lack Of Large-scale Standardized Datasetsmentioning
confidence: 99%
See 1 more Smart Citation